1997
DOI: 10.1029/97ja01448
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heavy ions on the high‐speed solar wind

Abstract: Abstract. We present the results of a p•rameter study of the influence of heavy ions on the background solar wind, choosing doubly ionized helium, or alpha particles, and O +•, as examples. Using a three-fluid solar wind model, we keep the input parameters to the electrons and protons unchanged and investigate the effects of changing the input energy flux to the heavy ions and their coronal abundance, i.e., their abundance at 1 R•, on the background electron-proton solar wind. Our results confirm earlier studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 28 publications
(14 reference statements)
1
28
0
1
Order By: Relevance
“…The faster O vi outflow velocity, together with the O vi kinetic temperatures that are much higher than the hydrogen temperatures (see above), suggest that the absorption of Alfvén waves at the ion cyclotron frequency, as proposed by several authors (e.g., Li et al 1997Li et al , 1999Tu & Marsch 1997;Cranmer et al 1999aCranmer et al , 1999bHu & Habbal 1999) to explain both the high kinetic temperatures and the high ion outflow velocities observed in coronal holes, might also occur inside streamers, at least above a certain height.…”
Section: Diagnostics Of Physical Parametersmentioning
confidence: 94%
“…The faster O vi outflow velocity, together with the O vi kinetic temperatures that are much higher than the hydrogen temperatures (see above), suggest that the absorption of Alfvén waves at the ion cyclotron frequency, as proposed by several authors (e.g., Li et al 1997Li et al , 1999Tu & Marsch 1997;Cranmer et al 1999aCranmer et al , 1999bHu & Habbal 1999) to explain both the high kinetic temperatures and the high ion outflow velocities observed in coronal holes, might also occur inside streamers, at least above a certain height.…”
Section: Diagnostics Of Physical Parametersmentioning
confidence: 94%
“…A high T p is a genuine property of these models, and thus flow velocities of up to 800 km s −1 are readily obtained within 10 R by a deposition of heat or momentum within a fraction of a solar radius above the Sun's surface. Li et al (1997) recently studied the influence of heavy ions on the fast wind in a three-fluid model in detail. They concluded that preferential heating of heavy ions, in particular of α particles, has an impact on the bulk flow that must be considered in wind models.…”
Section: Models With Hot Ions In the Inner Coronamentioning
confidence: 99%
“…In addition, the heavy ions are deduced to be significantly hotter and faster than the protons (Li et al 1997).…”
Section: Introductionmentioning
confidence: 99%